Peran Inovasi Keuangan Digital dalam Mendukung Efisiensi Pengelolaan Keuangan - Derita Telaumbanua; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to analyze and describe the role of digital financial innovation in supporting the efficiency of financial management at Alfamart Bawen, Semarang Regency, as a modern retail unit with a high transaction volume. The study focuses on how the implementation of digital financial innovations such as integrated point of sales systems, cashless payment methods, and digital-based financial reporting contributes to transaction recording efficiency, cash flow management, financial reporting accuracy, and internal control at the store level. To address these issues, the study draws upon theories of innovation, financial management, and technology acceptance within organizations. Data were collected through in-depth interviews, direct observation, and documentation at the Alfamart Bawen outlet, with informants selected purposively based on their direct involvement in financial management activities. The data were analyzed qualitatively using thematic analysis through the stages of data reduction, data display, and conclusion drawing. The findings indicate that digital financial innovation plays a strategic role in improving the efficiency of store-level financial management through the automation of transaction recording, enhanced accuracy and timeliness of financial reports, improved cash flow management, and strengthened internal control, although its effectiveness remains influenced by the readiness of human resources and the stability of supporting systems.